Stratum corneum lipidomics analysis reveals altered ceramide profile in atopic dermatitis patients across body sites with correlated changes in skin microbiome. Issue 10 (17th September 2020) - Emmert, Hila; Baurecht, Hansjörg; Thielking, Frederieke; Stölzl, Dora; Rodriguez, Elke; Harder, Inken; Proksch, Ehrhardt; Weidinger, Stephan
Abstract: Background: Atopic dermatitis (AD) is driven by the interplay between a dysfunctional epidermal barrier and a skewed cutaneous immune dysregulation. As part of the complex skin barrier dysfunction, abnormalities in lipid organization and microbiome composition have been described. We set out to systematically investigate the composition of the stratum corneum lipidome, skin microbiome and skin physiology parameters at three different body sites in patients with AD and healthy volunteers. Methods: We analysed tape strips from different body areas obtained from 10 adults with AD and 10 healthy volunteers matched for FLG mutation status for 361 skin lipid species using the Metabolon mass spectrometry platform. 16S rRNA data were available from all probands. Results: Our study showed that the lipid composition differs significantly between body sites and between AD patients and healthy individuals. Ceramide species NS was significantly higher in AD patients compared to healthy volunteers and was also higher in AD patients with a FLG mutation compared to AD patients without a FLG mutation. The correlation analysis of skin lipid alterations with the microbiome showed that Staphylococcus colonization in AD is positively correlated with ceramide subspecies AS, ADS, NS and NDS. Conclusion: This is the first study to reveal site‐specific lipid alterations and correlations with the skin microbiome in AD.